2024
DOI: 10.1021/acscentsci.3c01201
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Alloys Enhanced Metabolic Fingerprints for the Diagnosis of COPD and Exacerbations

Haiyang Su,
Yuanlin Song,
Shouzhi Yang
et al.

Abstract: Accurate diagnosis of chronic obstructive pulmonary disease (COPD) and exacerbations by metabolic biomarkers enables individualized treatment. Advanced metabolic detection platforms rely on designed materials. Here, we design mesoporous PdPt alloys to characterize metabolic fingerprints for diagnosing COPD and exacerbations. As a result, the optimized PdPt alloys enable the acquisition of metabolic fingerprints within seconds, requiring only 0.5 μL of native plasma by laser desorption/ionization mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…To validate the reliability of serum GDF15, we need to conduct more prospective, multi-center investigations in the future. Furthermore, a recent study has shown that constructing the mesoporous PdPt-assisted LDI MS for biomarker analysis results in a more accurate early diagnosis of COPD and AECOPD ( 47 ). In the future, we may be able to use this platform to detect serum biomarkers, such as GDF15 and ALB to identify malnutrition in patients with AECOPD to provide early nutritional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the reliability of serum GDF15, we need to conduct more prospective, multi-center investigations in the future. Furthermore, a recent study has shown that constructing the mesoporous PdPt-assisted LDI MS for biomarker analysis results in a more accurate early diagnosis of COPD and AECOPD ( 47 ). In the future, we may be able to use this platform to detect serum biomarkers, such as GDF15 and ALB to identify malnutrition in patients with AECOPD to provide early nutritional therapy.…”
Section: Discussionmentioning
confidence: 99%